ANALISIS EFISIENSI ALAT TANGKAP CANTRANG DI KABUPATEN PEMALANG, JAWA TENGAH - WARIDIN - (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2006)
Objective of this research are to analyze of efficiency (technique, alocative andeconomics) and to analyze return and expenditure on fish catching enterprise with usecantrang catch tool in Fish Trade Center (Tempat Pelelangan Ikan, TPI) at Asemdoyong,Pemalang Regency, Central Java. Use the simple random sampling methods; choose 100fisherman people as respondent. The analysis of data with stochastic frontier productionfunction using the Maximum Likelihood Estimation (MLE) Method.The result of estimation shows that majority fish catching enterprise use theCantrang catching tools, partly (50-90^) achieved technical efficiency. Average value oftechnical efficicieny is 0.619. Price and economic efficiency value each 1,612 and 1,922.Technically and economically, fish catching enterprise use the catrang tool not efficiencyyet, so that still probably increase or decrease production input allocation. Result of thestudy so indicate that the enterprise that done by fisherman still profitable like indicate byratio value of return cost ratio is 1,18.